The Climatology of Elevated Stratopause Events in the UA‐ICON Model and the Contribution of Gravity Waves. Issue 7 (9th April 2023) - Karami, Khalil; Borchert, Sebastian; Eichinger, Roland; Jacobi, Christoph; Kuchar, Ales; Mehrdad, Sina; Pisoft, Petr; Sacha, Petr
Abstract: The climatologies of the stratopause height and temperature in the UA‐ICON model are examined by comparing them to 17‐years (2005–2021) of Microwave Limb Sounder (MLS) observations. In addition, the elevated stratopause (ES) event occurrence, their main characteristics, and driving mechanisms in the UA‐ICON model are examined using three 30‐year time‐slice experiments. While UA‐ICON reasonably simulates the large‐scale stratopause properties similar to MLS observations, at polar latitudes in the Southern Hemisphere the stratopause is ∼8 K warmer and ∼3 km higher than observed. A time lag of about two months also exists in the occurrence of the tropical semiannual oscillation of the stratopause compared to the observations. ES events occur in ∼20% of the boreal winters, after major sudden stratospheric warmings (SSWs). Compared to the SSWs not followed by ES events (SSW‐only), the ES events are associated with the persistent tropospheric forcing and prolonged anomalies of the stratospheric jet. Our modeling results suggest that the contributions of both gravity waves (GW)s and resolved waves are important in explaining the enhanced residual circulation following ES events compared to the SSW‐only events but their contributions vary through the lifetime of ES events. We emphasize the role of the resolved wave drag in the ES formation as in the sensitivity test when the non‐orographic GW drag is absent, the anomalously enhanced resolved wave forcing in the mesosphere gives rise to the formation of the elevated stratopause at about 85 km. Plain Language Summary: Using 17 years (2005–2021) of Microwave Limb Sounder (MLS) observations, we show negative (cooling stratopause temperatures and decreasing stratopause heights) trends in most regions and seasons. The largest negative trend in the stratopause temperature (by considering all regions and all seasons) is found in the Southern Hemisphere (SH)'s polar region during austral spring. The seasonal average of cooling rates is comparable in the mid‐latitudes of Northern Hemisphere and SH. In the UA‐ICON simulations, the elevated stratopause events (ESEs) occur after major sudden stratospheric warmings (SSWs). ESEs frequency is 2 events per decade in UA‐ICON simulations. Our results show that the wind reversal is stronger and long‐lasting in the ESEs compared to SSW‐only events. In addition, the easterlies extend to the mesosphere in the composites of ESEs, but the reversed winds are limited to below 60 km in the case of SSW‐only events. We show that the non‐orographic gravity wave drag induces anomalous residual circulation after SSW that causes the ESEs. We also show that the ESEs form even in the absence of non‐orographic gravity wave drag. In this case, the anomalous residual circulation is due to the anomalously enhanced resolved wave forcing in the mesosphere that gives rise to the formation of the ESEs at about 85 km. Key Points: The largest stratopause trend is found in the Southern Hemisphere polar region during austral springbased on Microwave Limb Sounder observations The suppression of gravity waves in UA‐ICON reveals the importance of resolvedwaves and their ability to compensate missing drag In the polar regions, the simulated stratopause is too warm and the tropical semi‐annual oscillation is about two months out of phase